Return to Sports and Activity After Total Ankle Arthroplasty and Arthrodesis: A Systematic Review. (August 2020) - Johns, William L.; Sowers, Christopher B.; Walley, Kempland C.; Ross, Daniel; Thordarson, David B.; Jackson, J. Benjamin; Gonzalez, Tyler A.
Background: There is no consensus regarding participation in sports and recreational activities following total ankle replacement (TAR) and ankle arthrodesis (AA). This systematic review summarizes the evidence on return to sports and activity after operative management with either TAR or AA for ankle osteoarthritis (OA). Methods: A literature search of MEDLINE, EMBASE, CINAHL, and Cochrane Library databases was performed. Risk of bias of included studies was assessed using Methodological Index for Non-Randomized Studies (MINORS) criteria. Included studies reported sport and activity outcomes in patients undergoing TAR and AA, with primary outcomes being the percentage of sports participation and level of sports participation. Results: Twelve studies met inclusion criteria for analysis. There were 1270 ankle procedures, of which 923 TAR and 347 AA were performed. The mean reported patient age was 59.2 years and the mean BMI was 28 kg/m 2 . The mean follow-up was 43 months. Fifty-four percent of patients were active in sports preoperatively compared with 63.7% postoperatively. The mean preoperative activity participation rate was 41% in the TAR cohort, but it improved to 59% after TAR, whereas the preoperative activity participation rate of 73% was similar to the postoperative rate of 70% in the AA cohort. The most common sports in the TAR and AA groups were swimming, hiking, cycling, and skiing. Conclusion: Participation in sports activity was nearly 10% improved after operative management of ankle OA with TAR and remains high after AA. The existing literature demonstrated a large improvement in pre- to postoperative activity levels after TAR, with minimal change in activity after AA; however, AA patients were more active at baseline. The most frequent postoperative sports activities after operative management of ankle OA were swimming, hiking, cycling, and skiing. Participation in high-impact sports such as tennis, soccer, and running was consistently limited after surgery. This review of the literature will allow patients and foot and ankle surgeons to set evidence-based goals and establish realistic expectations for postoperative physical activity after TAR and AA. Level of Evidence: Level III, systematic review.